Anticancer Effect of Tanshinones on Female Breast Cancer and Gynecological Cancer - Jin, Zhou; Chenghao, Yu; Cheng, Peng (Frontiers in Pharmacology, 2022)
Female breast cancer, ovarian cancer, cervical cancer and endometrial cancer are the most common tumors and the most common cause of cancer-related mortality worldwide in women. Drugs derived from natural plants play important roles in malignant tumor therapy. Salvia miltiorrhiza is a commonly used Chinese herb, which has been used in the treatment of liver diseases and cardiovascular diseases because of its positive effect of promoting blood circulation, increasing oxidative stress and removing blood stasis. Recently studies have found that fat-soluble components of Salvia miltiorrhiza such as Tanshinone II, Tanshinone I, Cryptotanshinone and Dihydrotanshinone I displayed good antitumor activity in vivo and in vitro for gynecological cancer by different molecular mechanisms. In this paper, the latest research progress on the antitumor effect and mechanism of Tanshinone compounds in breast cancer and gynecological cancer was reviewed to provide references for the research and clinical application of these compounds (Tanshinone II, Tanshinone I, Cryptotanshinone and Dihydrotanshinone I).